Exploring the impact of scientific research through citation analysis tools in policies and guidelines (Journal of EAHIL, 2025)
Research impact has traditionally been measured through academic citations. In recent years, however, the focus has shifted towards assessing the broader effects of research on society, including its influence on policy-making and clinical guidelines. This brief article explores the role of citation analysis, extending impact measurement beyond academia. Using data from Scival Impact Module, we demonstrate how scientific publications from our institution have influenced policy documents and guidelines. We argue that these tools are essential in recognising the real-world value of research, providing meaningful indicators for evaluation and accountability. KeywordsResearch impact; Citation analysis; Policy documents; Guidelines; Altmetrics; Bibliometrics